2015
DOI: 10.1128/jcm.00624-15
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Lipoarabinomannan and Xpert MTB/RIF Testing in Cerebrospinal Fluid To Diagnose Tuberculous Meningitis in an Autopsy Cohort of HIV-Infected Adults

Abstract: i Point-of-care tests for tuberculous meningitis (TBM) are needed. We studied the diagnostic accuracy of the lipoarabinomannan (LAM) lateral flow assay (LFA), LAM enzyme-linked immunosorbent assay (ELISA), and Xpert MTB/RIF in cerebrospinal fluid (CSF) in an autopsy cohort of Ugandan HIV-infected adults. We obtained written informed consent postmortem from the next of kin. A complete autopsy was done and CSF obtained. We performed LAM LFA (on unprepared and supernatant CSF after heating and spinning), LAM ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The detection of lipoarabinomannan (LAM), for instance, a Mycobacterium-specific liposaccharide from the Mtb cell wall, is an example of the basis of a well-studied commercial ELISA assay that shows promise for its diagnostic use in urine with a reported sensitivity of 74% and specificity of 86.9% in a study performed on 148 confirmed TB patients (Tessema et al, 2001); a sensitivity of 80.3% and specificity of 99% in a study conducted on 132 confirmed TB patients (Boehme et al, 2005); and a sensitivity of 44% and specificity of 89% in a study conducted on 195 TB-positive patients in a high-HIV prevalence setting (Mutetwa et al, 2009). Within TBM cases (see Box 1), the direct LAM-ELISA assay of CSF has similarly shown a sensitivity of 64% and specificity of 86.9% in a study including 50 TBM cases in a high-HIV-prevalence setting (Patel et al, 2009); and a sensitivity of 43% and specificity of 91% for definite TBM cases in a study performed on CSF collected from the 4th ventricle, post-mortem (Cox et al, 2015). However, Bahr et al (2015) determined that this LAM-based TB antigen test yielded negative results for all the CSF samples (∼100) analyzed in their study, of whom 18 had a confirmed diagnosis of TBM.…”
Section: Urine Reflects Dysbiosis Within Bacterial Cns Infection(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of lipoarabinomannan (LAM), for instance, a Mycobacterium-specific liposaccharide from the Mtb cell wall, is an example of the basis of a well-studied commercial ELISA assay that shows promise for its diagnostic use in urine with a reported sensitivity of 74% and specificity of 86.9% in a study performed on 148 confirmed TB patients (Tessema et al, 2001); a sensitivity of 80.3% and specificity of 99% in a study conducted on 132 confirmed TB patients (Boehme et al, 2005); and a sensitivity of 44% and specificity of 89% in a study conducted on 195 TB-positive patients in a high-HIV prevalence setting (Mutetwa et al, 2009). Within TBM cases (see Box 1), the direct LAM-ELISA assay of CSF has similarly shown a sensitivity of 64% and specificity of 86.9% in a study including 50 TBM cases in a high-HIV-prevalence setting (Patel et al, 2009); and a sensitivity of 43% and specificity of 91% for definite TBM cases in a study performed on CSF collected from the 4th ventricle, post-mortem (Cox et al, 2015). However, Bahr et al (2015) determined that this LAM-based TB antigen test yielded negative results for all the CSF samples (∼100) analyzed in their study, of whom 18 had a confirmed diagnosis of TBM.…”
Section: Urine Reflects Dysbiosis Within Bacterial Cns Infection(s)mentioning
confidence: 99%
“…Despite all efforts toward improved solutions to curbing TB since the discovery of Mtb as the causative agent in 1882, there is still a very limited understanding of Mtb infection within the host, especially so for TBM, and hence the need for new biomarkers better describing this. use on CSF for diagnosis of TBM, and also discussed the study by Cox et al (2015). Ultimately, the LAM-ELISA, like many other TB diagnostic tests, is not sufficient as a stand-alone assay for a definitive diagnosis of TB.…”
Section: Urine Reflects Dysbiosis Within Bacterial Cns Infection(s)mentioning
confidence: 99%
“…In a proof-of-concept study, LAM enzyme-linked immunosorbent assay (ELISA) testing of CSF on a cohort of South African adults with suspected TBM had a sensitivity of 64% and a specificity of 69% for the diagnosis of culturepositive TBM (8). An autopsy study of LAM LFA for the diagnosis of definite TBM showed a sensitivity of 75% and a specificity of 87% (9). There has been no report of LAM LFA on urine or CSF in living patients for the diagnosis of TBM.…”
mentioning
confidence: 99%
“…The unique characteristic of the test is that its sensitivity increases as CD4 T-cell count falls, with a sensitivity of 56% in those with CD4 <100 cells/ml 56 . Yet, in CSF, despite some initial optimism related to an autopsy-based study in Uganda, the Alere TB-LAM has shown poor sensitivity on lumbar CSF in Uganda 85,86 , along with a larger Zambian study which examined culture positive TBM in Zambia (TB-LAM sensitivity 22% (23/105)) 85, 87 . The Alere TB-LAM is also limited by is susceptibility to individual reader interpretation of the darkness of the test line compared to the reference card (Figure 4).…”
Section: Pathogen-based Biomarkersmentioning
confidence: 99%